Advanced introduction to political trust - Newton, Kenneth 1940- (Edward Elgar Publishing, 2024)
Newton investigates cutting-edge current research and pathways for future research in the field, presenting empirical studies highlighting political trust's importance, variations, origins and consequences. He demonstrates that political trust is a useful and highly important symptom, but not a cause, of political conditions. Through exploration of the relationship between political trust and democracy, Newton illustrates that functions often attributed to political trust alone may be carried out by non-political institutions and practices instead
Literaturverzeichnis: Seite 122-138, Register
Keywords: Politik; Vertrauen; Lehrbuch